1978
DOI: 10.1002/iroh.19780630204
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Changes in Biomass of Riverbed Periphyton

Abstract: Periphytic biomass in a downriver riffle of the Grand River in Southern Ontario, Canada was measured with concrete-block glass slide samplers from May to December 1971. Average rate of accumulation of periphyton on glass slides was 266.2 mg/m2/day ash-free weight, 120.9 mg/m2/day carbon, 20.4 mg/mz/day nitrogen, or 1.11 mg/mZ/day chlorophyll a and on concrete blocks was 590.0 mg/mZ/day ash-free weight, 202.9 mg/mZ/day carbon, 22.8 mg/m2/day nitrogen, or 2.95 mg/ mz/day chlorophyll a. The standing biomass of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
(9 reference statements)
1
9
0
2
Order By: Relevance
“…The relationship between AFDW and chlorophyll a of periphytic matter was very similar to that found by Liaw & MacCrimmon (1978) . During colonization the chlorophyll a content decreased with increasing periphyton accumulation .…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The relationship between AFDW and chlorophyll a of periphytic matter was very similar to that found by Liaw & MacCrimmon (1978) . During colonization the chlorophyll a content decreased with increasing periphyton accumulation .…”
supporting
confidence: 71%
“…During colonization the chlorophyll a content decreased with increasing periphyton accumulation . Liaw & MacCrimmon (1978) attributed this finding to changes in physical factors, e .g., light and temperature. In Vasikkalampi pond this relationship between AFDW and chlorophyll a appeared to be related to changes in the proportion of animals associated with the periphytic material .…”
mentioning
confidence: 99%
“…These parameters should be measured in studies of community metabolism because of their direct bearing on photosynthesis and respiration. When either the chemical or the geomorphic parameters were used with PAR, temperature, and chlorophyll a; the equations incorporating geomorphic parameters were slightly more precise and accounted for 83-98% of the variance 31 PA Liaw & MacCrimmon 1978Grzenda & Brehmer 1960Hornberger et al 1977Sumner & Fisher 1979Fisher & Carpenter 1976Fisher & Likens 1973Naiman 1983Naiman 1983Naiman 1983Naiman 1983Naiman 1983 This study a Data in parentheses converted from originally reported values using one or more of the following factors as necessary: P.Q. = 1.2, R.Q.…”
Section: Measure Of Distance Between Stationsmentioning
confidence: 99%
“…Exemplos de estudos ecológicos envolvendo a análise de comunidades de produtores associadas a substratos artificiais em ambientes lóticos são relativamente comuns na literatura mundial (Biggs, 1988;Liaw & Maccrimmon, 1978;Leland & Carter, 1985;Clifford et al, 1992;Barbee, 2005). Vários estudos semelhantes são encontrados para rios e riachos brasileiros (Lobo & BuselatoToniolli, 1985;Oliveira et al, 2002;Mendes & Barbosa, 2002;Fernandes & Esteves, 2003;Skinner & Coutinho, 2005;Lobo et al, 2004).…”
Section: ) Introduçãounclassified